On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae) - Grandinete, Yuri Campanholo [UNESP] (2019)
The genus Gastrodynerus is here revised based on external morphology and male genitalia. Bohart (1984) proposed Gastrodynerus as a new genus with three species: G. vanduzeei (Bohart 1948), G. searsi Bohart, 1984, and G. stangei Bohart, 1984. Later, Rodriguez-Palafox (1996) added G. tacubayae (de Saussure, 1857). Herein, we describe four new species from Central America and South America: G. guatemalensis sp. nov.; G. barretti sp. nov.; G. aimara sp. nov. and G. yungaensis sp. nov. After this taxonomic revision, the Gastrodynerus includes eight species widely distributed in the New World. An identification key is provided for all of the species.